2018
DOI: 10.1155/2018/6470957
|View full text |Cite
|
Sign up to set email alerts
|

MST1 Suppression Reduces Early Brain Injury by Inhibiting the NF-κB/MMP-9 Pathway after Subarachnoid Hemorrhage in Mice

Abstract: Background Mammalian sterile 20-like kinase 1 (MST1), the key component of the Hippo-YAP pathway, exhibits an important role in the pathophysiological process of various neurological disorders, including ischemic stroke and spinal cord injury. However, during subarachnoid hemorrhage, the involvement of MST1 in the pathophysiology of early brain injury remains unknown. Methods We employed intravascular filament perforation to establish the subarachnoid hemorrhage (SAH) mouse model. The MST1 inhibitor XMU-MP-1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…However, supporting KINOMEscan profiling data within this same study reported that XMU-MP-1 has a strong affinity to inhibit an additional 21 kinases [ 8 ]. Despite this, follow-up studies have since claimed to have successfully utilised XMU-MP-1 to specifically target Hippo signalling, highlighting protective applications against early brain injury [ 9 ] and cardiac pressure overload [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, supporting KINOMEscan profiling data within this same study reported that XMU-MP-1 has a strong affinity to inhibit an additional 21 kinases [ 8 ]. Despite this, follow-up studies have since claimed to have successfully utilised XMU-MP-1 to specifically target Hippo signalling, highlighting protective applications against early brain injury [ 9 ] and cardiac pressure overload [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, this Src‐MST1‐IκBα signaling forms the critical player in microglial activation and ultimately neuronal death (Zhao et al, ). Hyperactivation of Hippo signaling has also been associated with several other stroke‐like conditions including traumatic brain injury (TBI) (Liang et al, ), subarachnoid hemorrhage (SAH) (Qu et al, ), and intracerebral hemorrhage (ICH) (Zhang et al, ).…”
Section: Disease Implications Of the Hyperactivated Hippo Pathwaymentioning
confidence: 99%
“…Furthermore, it has been demonstrated that stroke‐induced brain injury mitigates upon specific deletion of microglial MST , exhibiting the therapeutic potential of MST in stroke and other microglial activation‐mediated neurological disorders (Zhao et al, ). In SAH mouse model, intraperitoneal injection of the MST1 inhibitor, Xmu‐mp‐1, and intracerebroventricular injection of MST1 shRNA reduced neuroinflammation, improved blood–brain barrier (BBB) disruption, brain edema, and white matter injury by inhibiting the NF‐ κ B/MMP‐9 pathway (Qu et al, ). Inhibition of MST1 via drug Xmu‐mp‐1 or via MST1 shRNA in ICH‐established SD rat model was also found to have decreased neuronal death.In addition, MST1 deficiency also repaired BBB damage, reduced brain edema, and improved neurobehavioral impairments, thereby highlighting MST1 as a suitable target for stroke therapeutics (Zhang et al, ).…”
Section: Disease Implications Of the Hyperactivated Hippo Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] Currently, it has been shown that MMP-9 plays a very important two-way role in the central nervous system, and that can be either the intermediate between pathological pathways or the central player in the regeneration of the central nervous system. 19,20 MMP-9 can open the blood-brain barrier and increase its permeability. It has previously been proposed that ECT increases bloodbrain barriers permeability in cerebrovascular.…”
Section: Introductionmentioning
confidence: 99%